Level of brand commitment among consumers of local cosmetic products in Melaka / Norazmira Mohd Dzahaimi - Mohd Dzahaimi, Norazmira (Faculty of Business and Management, 2018)
This research is done to study the level of brand commitment among consumers of local cosmetics product in Melaka. There are four factors that includes in this study which influenced the level of brand commitment of local cosmetic consumers such as brand affect, brand image, brand trust and brand value. This study is focusing on the population of both men and women who are living in Melaka. For about 150 individuals are selected to be the respondents for this study. The researcher used purposive or known as judgmental sampling method for completing this study. The findings of this study shows that brand trust is the most influential factor that influenced the changes in brand commitment among local cosmetic consumers in Melaka. The data analysis of correlation and regression is done by using SPSS 2.0 software.